KONTAMINASI KAPANG Aspergillas sp DAN AFLATOKSIN PADA KACANG TANAH SEBAGAI BAHAN DASAR BUMBU PECEL YANG DIJUAL PEDAGANG KELILING DI KOTA SEMARANG - Martini -; Pujianto -; Cindy Kusumawardhani (Jurnal Kesehatan Masyarakat Indonesia, 2005)
Background: As a small entrepreneur, pecel vendors do not have much capital to run their business. Therefore, peanuts bought as the base for pecel is low in quality. This low quality peanut is potential to be contaminated by aspergillus sp. Purpose: this research is aimed to see whether there is a contamination of aspergillus sp in peanuts asthe base for making the peanut sauce (bumbu pecel) sold by pecel vendors in the cigt of Semarang. Method: this research is a cross sectional suryey conducted by interviewing 32 pecel vendors. 100 gr ofpeanuts were acquiredfrom the vendors to be examined for the presence of aspergillus sp and a/latoxin. To measure the ability to produce aJlatoxinis by exposing thefungus under ultra violet rays. Results: from 32 surveys, all ofthevendors arefemale, has very low educational level (never have any formal education or only graduated from elementary school). The vendors are not from Semarang and have low understanding in personal hygiene (8,/.2%0). The contamination of aspergillus flavus in peanuts used as the base for peanut sauce has the value of 100% both derivedfrom the low quality peanuts and also from the low level of hygiene among the street vendors. Conclusion: fungus contamination especially aspergillus sp can easily happened in peanuts. There should be an improvement in the level of hygiene and food handling among pecelstreet vendors in Semarang.Keywords : Aspergillus, Aflatoxin, peanuts, pecel